P38 Assessing the repeatability of NT-proBNP testing using laboratory and point of care testing in PAH (REPEAT-PAH). (11th November 2022) - Durrington, C; Battersby, C; Holt, L; Fairman, A; Salisbury, T; Turton, H; Watson, L; Hameed, AG; Charalampopoulos, A; Elliot, CA; Rothman, AMK; Middleton, J; et al.
Abstract : Introduction: N-terminal pro brain natriuretic peptide (NT-proBNP) is an important biomarker in the monitoring of patients with pulmonary arterial hypertension (PAH) and is included in multiple risk stratification tools. However, results are rarely available at the time of clinical assessment. We aimed to examine the reliability of point of care testing (POCT), explore its potential role in remote monitoring and the effect exercise may have on NT-proBNP in the context of PAH. Methods: For this prospective study of group 1 PAH, patients attended 2 visits – a 'rest' or an 'exercise' visit including an incremental shuttle walk test. PAH was haemodynamically defined by a mean pulmonary artery pressure >20 mmHg, pulmonary artery wedge pressure ≤15 mmHg and pulmonary vascular resistance > 3 WU. NT-proBNP laboratory and POCT samples were taken pre- and post- either rest or exercise, and a further postal laboratory sample was sent back to the department through the postal service and processed to simulate conditions of remote monitoring. Results: An interim review of 37 patients found a strong correlation between POCT and laboratory NT-proBNP (r 2 0.945, p<0.001) and laboratory and the delayed processed postal NT-proBNP samples (r 2 0.994 p<0.001). Less agreement was noted between POCT and laboratory NT-proBNP at higher values. This is demonstrated in the figure below, with data stratified by ESC/ERS risk group. There was no significant difference demonstrated between pre- and post- exercise laboratory samples (p=0.88). Conclusion: This preliminary analysis suggests that POCT with NT-proBNP provides an alternative to laboratory NT-proBNP analysis in the risk stratification of patients with PAH. Laboratory NT-proBNP was not affected by exercise. Furthermore, delayed analysis of samples delivered by post to the laboratory did not significantly impact results suggesting a role for the use of NT-proBNP in remote monitoring. Please refer to page A213 for declarations of interest related to this abstract.